Dopamine-modified TiO2 monolith-assisted LDI MS imaging for simultaneous localization of small metabolites and lipids in mouse brain tissue with enhanced detection selectivity and sensitivity. Issue 5 (29th March 2017) - Wu, Qian; Chu, James L.; Rubakhin, Stanislav S.; Gillette, Martha U.; Sweedler, Jonathan V.
Abstract : A dopamine-modified TiO2 monolith was developed to assist LDI MS imaging for small metabolites and lipids simultaneously with enhanced sensitivity. Abstract : Localization of metabolites using multiplexed mass spectrometry imaging (MSI) provides important chemical information for biological research. In contrast to matrix-assisted laser desorption/ionization (MALDI), TiO2 -assisted laser desorption/ionization (LDI) for MSI improves detection of low molecular mass metabolites (<500 Da) by reducing matrix background. However, the low UV absorption of TiO2 nanoparticles and their ester hydrolysis catalytic activity hinder the detection of phospholipids and many low-abundance molecules. To address these challenges, we evaluated and optimized the material morphology and composition of TiO2 . Dopamine (DA) was found to be an efficient ligand for TiO2, resulting in increased UV light absorption, higher surface pH, and formation of monolithic TiO2 -DA structures. The sub-micron scale and higher surface pH of the TiO2 particle sizes led to improved detection of phospholipid signals. Compared to unmodified TiO2 sub-micron particles, the DA-modified TiO2 monolith led to 10- to 30-fold increases in the signal-to-noise ratios of a number of compound peaks. The TiO2 -DA monolith-assisted LDI MSI approach has higher selectivity and sensitivity for Lewis basic compounds, such as fatty acids, cholesterols, ceramides, diacylglycerols, and phosphatidylethanolamine, when analyzed in positive mode, than traditional MALDI MS. Using this new method, over 100 molecules, including amino acids, alkaloids, free fatty acids, peptides, and lipids, were localized in mouse brain sections. By comparing the presence and localization of those molecules in young and old mouse brains, the approach demonstrated good performance in the determination of aging-related neurochemical changes in the brain.